Development and verification of an adjustment factor for determining the axial length using optical biometry in silicone oil-filled eyes - Auffarth, Gerd U.; Naujokaitis, Tadas; Blöck, Louise; Daghbashyan, Anna; Meis, Jan; Augustin, Victor A.; Khoramnia, Ramin; Yildirim, Timur Mert (Diagnostics, 2022)
The aim of this prospective clinical study was to establish and verify an adaptation for axial length (AL) measurement in silicone oil (SO)-filled pseudophakic eyes with a Scheimpflug and partial coherence interferometry (PCI)-based biometer. The AL was measured with a Pentacam AXL (OCULUS Optikgeräte GmbH, Wetzler, Germany) and IOLMaster 700 (Carl Zeiss Meditec, Jena, Germany). The coefficients of variation (CoV) and the mean systematic difference (95% confidence interval (CI)) between the devices were calculated. After implementing a setting for measuring AL in tamponaded eyes with a Pentacam based on data of 29 eyes, another 12 eyes were examined for verification. The mean AL obtained with the Pentacam was 25.53 ± 1.94 mm (range: 21.70 to 30.76 mm), and with IOLMaster, 24.73 ± 1.97 mm (ranged 20.84 to 29.92 mm), resulting in a mean offset of 0.80 ± 0.08 mm (95% CI: 0.77, 0.83 mm), p < 0.001. The AL values of both devices showed a strong linear correlation (r = 0.999). Verification data confirmed good agreement, with a statistically and clinically non-significant mean difference of 0.02 ± 0.04 (95% CI: −0.01, 0.05) mm, p = 0.134. We implemented a specific adaptation for obtaining reliable AL values in SO-filled eyes with the Pentacam AXL.
Gesehen am 07.09.2022